SISTEM PENDUKUNG KEPUTUSAN SELEKSI CALON TARUNA PRAMUGARA PADA AEROSPACE TRAINING CENTRE MENERAPKAN METODE PROMETHEE II - Sidabutar, Rudi; Mesran, Mesran; Sitompul, Noferianto (STMIK Budi Darma, 2018)
Selection Candidate steward taruna represent one of [the] way of used to select steward taruna candidate [so that/ to be] as according to quality of which [is] wanted. Steward represent one of [the] profession [in] service activities area at one particular good company [of] air, sea and also land. A steward undertake to give service, taking care of security, and safety [of] passenger during air transport which underway and also have very high work risk and each;every steward have to have candid behavior in running each;every its work. Expected Candidate steward taruna selection is not easy to, because decision making accepted or [do] not it [him] steward taruna candidate still [done/conducted] by llama that is pursuant to previous ladder national test value. This matter result inaccurate selection decision making and its inappropriate result and fall wide of the mark, [is] for that needed [by] decision supporter system which later assist decision making. With existence of decision supporter system very required [so that/ to be] can assist to take correct decision in determining steward taruna candidate selesksi [at] Aerospace Training Centre.Â Keyword: SPK, taruna, steward, aerospace